1990
DOI: 10.1007/bf01185954
|View full text |Cite
|
Sign up to set email alerts
|

Crack tip fields in ductile crystals

Abstract: Abstract.Results on the asymptotic analysis of crack tip fields in elastic-plastic single crystals are presented and some preliminary results of finite element solutions for cracked solids of this type are summarized. In the cases studied, involving plane strain tensile and anti-plane shear cracks in ideally plastic fc c and b c c crystals, analyzed within conventional small displacement gradient assumptions, the asymptotic analyses reveal striking discontinuous fields at the crack tip.For the stationary crack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(16 citation statements)
references
References 17 publications
(36 reference statements)
2
14
0
Order By: Relevance
“…Rice also established several features for equilibrium stress distribution around a crack tip that are important to the present analysis; these will be summarized in the next section. Rice et al's [2] finite element analysis confirmed the crystal slip pattern obtained in the asymptotic analysis [1].…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Rice also established several features for equilibrium stress distribution around a crack tip that are important to the present analysis; these will be summarized in the next section. Rice et al's [2] finite element analysis confirmed the crystal slip pattern obtained in the asymptotic analysis [1].…”
Section: Introductionsupporting
confidence: 68%
“…Rice [1] found an asymptotic stress field around the crack tip, which gives the stresses ahead of the crack as ~rlll0___o --2x/~r = 4.90% az210=0 = 3v/6r = 7.35% O"1210=0 : 0, (1) where 7-is the critical resolved shear stress for the primary slip systems {1 1 1}(1 1 0) in fcc crystals. This field occurs around the tip of an external crack in a perfectly plastic crystal and was verified by Rice et al's [2] finite element analysis. Based on the limit analysis, Rice [1] found another asymptotic field that may occur around the tip of an internal crack in a crystal and gave the stresses ahead of the crack tip as Crlllo=o : 0, crz2lo=o = x/67-= 2.457-, ~lzlo=o : 0.…”
Section: Introductionmentioning
confidence: 73%
“…As the crack tip stress field becomes more intense, additional transverse planes allow for through-thickness slip of dislocations. This evolution is similar to the plane strain to plane stress transitions that occur in single crystals [33]. While this trend appears in both nano-and micrograined textured films, there is an important grain-coarsening phenomenon that is enabled by cyclic plastic deformation.…”
mentioning
confidence: 53%
“…The macroscopic slip is calculated by averaging the microscopic slip at every Gauss point in the mesh. This model has been successfully used to model the tensile deformation of both BCC and FCC crystals [75], and later to study stationary cracks [76]. A more detailed description of the constitutive relation used to model the double slip phenomenon has been discussed [42][43][44].…”
Section: Modeling Of Crack Closure Within a Grainmentioning
confidence: 99%